IMPLEMENTASI PERMENDIKNAS NOMOR 49 TAHUN 2007 TENTANG PERENCANAAN PROGRAM OLEH BEC KAMPUNG INGGRIS PARE KEDIRI - SAHRONI, MAHMUD (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2016)
The Standard Program in The Minister of National  Education Regulations (Permendiknas) Number 49 of  2007 on the standard management of nonformal education  is formed by the government with the purpose of enhancing the role of nonformal education in the national education system. The standard planning of this program includes the standard vision, mission, purpose and the work plan. BEC as one of the first English institutions in English Village has authority on organization planning of education, and it becomes director’s commitment of BEC that BEC was designed to become independent institution. As result,  planning program is developed by the director. The purposes of this research are to 1) Explaining the implementation of Permendiknas No. 49 Year 2007 about the planning of program by the course institution, BEC Pare Kediri.; 2) Explaining the obstacles that have been faced by the institution, BEC in implementing Permendiknas No.49 year 2007; 3) Explaining the strategies of BEC as a course institution in overtaking the obstacles regarding the program planning according to Permendiknas No.49 year 2007. This research is a research on the policies that uses the qualitative, descriptive and analytic approach. The data collection is done through interviews, observation and documentation. The analytic techniques used are the analytic descriptive and the data validation techniques using the triangulation and member check. This research can be concluded as the followings: 1) BEC has implemented 74 % program planning on Permendiknass No.49 year 2007; 2) The obstacles faced by BEC in implementing Permendiknas No. 49 year 2007 are the inadequate human resources in planning the program planning. It is obvious because the role of Mr. Kalend is too dominant in establishing the program planning. Meanwhile the role of teacher and the educational staffs is still lacking. The variety of students’ characteristics as the consumers of BEC are also affecting the establishment and the determination of planning program as forced to be able to accommodate most of the BEC’s consumers. The society and the government are still far from enough in giving advices and supporting BEC in establishing the planning program; 3) the efforts of BEC in overcoming the obstacles are by determining several policies that form and promote teachers from the alumnus of BEC.  Direct observation and analysis towards consumers or society are done in order to get the thing that expected by consumers or society when learning English. Finally BEC use self-sufficiency on every aspect to hide dependence from government or society. Keywords : policy implementation, curriculum based environment, program                              Adiwiyata